Unveiling the modulation of SAMHD1 in the differentiation of follicular helper T cells and the impact of HIV infection - Moura, Rita Diniz de (2022)
Tese de mestrado, Microbiologia Clínica e Doenças Infecciosas Emergentes, Universidade de Lisboa, Faculdade de Medicina, 2022